POLA SPASIAL PERMUKIMAN DESA PANTAI GALESONG - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Galesong is a coastal village which is located on the coast of Makassar straits. It has double natural resourches that are agriculture and sea fishery. The characteristic of the coastal village Galesong is atraditional settlement with staging house generally, in habitants still have a familyrelationship. They usually involve their family in production process, distribution, and consumption. Village in habitantsstill bound to religious tradition. The objective of study is to find out of the description of spatial pattern of Galesong Village. Secondly factor which influence its settlement and how those factors influence spatial pattern of this settlement. This study applies qualitative approach. Firstly, the researcher observes the whole areas, then decides the material of this research, and the spatial border of houses are done in the location of the research. The researches, then analyzes all group of houses (six groups) reference theories and other conditions support the result of the research. The result of this research can be devided into two categories. Firstly, Spatial pattern of group of houses in Galesong coastal village it also can be devided into two parts (a) Houses grow extensively in a group in which they create open spaces with composition of houses don't close each. The houses are seperated by paasageway between houses. (b) Houses grow closely and they are oriented the street as a main access. Secondly, The general spatial pattern of Galesong Settlement is the group of houses create open spaces. The open spaces have a funtion to relate group of houses with other group houses are in their sorrounding. In the further research, the researcher finds out the pattern of growing houses process. The houses actually grow in lines from the south to the north (the group of houses in the south are older that the group of houses in the north) and they don't grow in order. On the contrary, the group of houses that grow more closely to infra structure of house composition become more in order. Factors that influence estabilishing pattern are socio-cultural and geographical condition in the society of Galesong Village.